Toward waterborne protozoa detection using sensing technologies - Nemati, Sara; Shalileh, Farzaneh; Mirjalali, Hamed; Omidfar, Kobra (Frontiers in Microbiology, 2023)
Drought and limited sufficient water resources are the main challenge of humankind during the coming years. The lack of water resources for washing, bathing, and drinking increases the use of unhealthy waters and risk of waterborne diseases. A considerable number of waterborne outbreaks are due to protozoan parasites that may remain active/alive in harsh environmental conditions. Therefore, regular monitoring program of water resources using sensitive techniques is needed to decrease the risk of waterborne outbreaks. Well-organized point of care (POC) system with enough sensitivity and specificity is the grail of research for monitoring platforms. In this review, we comprehensively gathered and discussed rapid, selective, and easy-to-use biosensor and nanobiosensor technology, which are developed for early detection of common waterborne protozoa.